The Role of Islamic Banks in Development of Halal Tourism: Evidence from Central Java Indonesia - Ismanto, Kuat; Fachrurazi, Fachrurazi; Mas'ad, Muhammad Aunurrochim (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2022)
Halal tourism has become a business trend in various countries, including Indonesia. Its existence requires the support of various sharia-based financial institutions, such as Islamic banks. However, its role in this industry has not yet been seen in the regions. The purpose of this paper is to analyze the role and position of Islamic banks in the development of halal tourism, especially in regions in Indonesia. This research was conducted in Central Java which includes three cities, namely Pekalongan City, Semarang City, and Surakarta City. Two types of data are needed in this study, both primary and secondary. Data were collected through observations at destinations, and interviews with Islamic banks and tourism business actors. Secondary data is collected through the assessment of documents, such as journal articles, books, research reports, and websites. The results of this study show that Islamic banks are an important part of regional halal tourism which acts as a supporting facility in the form of institutions. The role of Islamic banks in the development of halal tourism has not been maximized, because there has not been good cooperation with tourism business actors. However, existing Islamic banks have played an indirect role well for tourism business actors (SMEs) and visitors. The position of Islamic banks in the development of regional halal tourism is as a supporting facility. In the halal tourism ecosystem, Islamic banks are part of the ecosystem. This study implies that halal tourism will develop quickly if it is supported by Islamic banks that play a special role in supporting the implementation of halal tourism.